Going fully digital: Perspective of a Dutch academic pathology lab - Nikolas Stathonikos; Mitko Veta; André Huisman; Paul J van Diest (Elsevier, 2013)
During the last years, whole slide imaging has become more affordable and widely accepted in pathology labs. Digital slides are increasingly being used for digital archiving of routinely produced clinical slides, remote consultation and tumor boards, and quantitative image analysis for research purposes and in education. However, the implementation of a fully digital Pathology Department requires an in depth look into the suitability of digital slides for routine clinical use (the image quality of the produced digital slides and the factors that affect it) and the required infrastructure to support such use (the storage requirements and integration with lab management and hospital information systems). Optimization of digital pathology workflow requires communication between several systems, which can be facilitated by the use of open standards for digital slide storage and scanner management. Consideration of these aspects along with appropriate validation of the use of digital slides for routine pathology can pave the way for pathology departments to go "fully digital." In this paper, we summarize our experiences so far in the process of implementing a fully digital workflow at our Pathology Department and the steps that are needed to complete this process.